(untitled) (Tribhuvan University Journal of Microbiology, 2018)
Objectives: The present study was conducted to determine the intestinal parasitosis among the school children of Kathmandu, Nepal. Methods: This study was carried out from February 2018 to May 2018. During the study, a total of 194 stool samples were collected from school going children of age above 5 years to below 15 years old and processed in Padma Kanya microbiology laboratory. The detection technique used for the parasites was concentration technique (Formal-ether Sedimentation method) and iodine mount was used for slide preparation. Data were entered into SPSS and analysis was done employing Chi square test. Result: Among 194 total cases, 12.4% (24/194) children were infected with parasites where female were highly infected (70.8%) and children of age group 9-11 were highly infected (58.3%).Parasitic infection was high in non-vegetarian children (83.3%) than vegetarian, symptomatic cases (66.7%, 16/24) than asymptomatic cases, public school (66.7%, 16/24) compared with private school, higher in children who don’t wash hands with soap before meal (87.5%) than who wash hands before meal and in children not taking anti helminthic drugs (95.8%) than children taking anti-helminthic drugs recently within six months. Further, children using direct tap water for drinking purpose were highly infected than others. Conclusion: The parasitic infection among school children was found closely related to their health hygiene, sanitary condition, water consumption and other activities.